Fintech and Impulse: How Payment Technology is Changing the Way Cirebon Young Society Shop - Budi Rusdian; Rita Kusumadewi; Atiatul Maollah; Arphandee Hasan (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This study evaluates the impact of payment technology such as fintech payment could change the way young society shop and increase the emergence of impulse purchases with all its convenience. This research aims to explore how these fintech payment contribute to the growth and stability of the market.impulsive Methods: This study using a quantitative using SEM analysis approach with a sample size of 100 respondents. The SmartPLS programs were used to analyze the data collected for this study. tConvergent validity was examined using outer loading and AVE, and used Cronbach’s Alpha and Composite Reliability (rho_a and rho_c) as indicators of internal consistency. This study also utilizing a literature review approach and examines the impact of fintech payment and impulse buying on young society consumptive behavior, as the population. Results: The result show that fintech payment and impulse buying positively and significantly affected consumptive buying partially and simultaneously. Fintech payments have a very small influence on consumptive behavior and credit card use has the highest contribution on consumptive behavior Conclusion and suggestion: The research results shows that many young people are still unaware of the consequences of all the conveniences provided, and that all conveniences inevitably come with sacrifices. Young society in Cirebon should be given knowledge about financial literacy and financial management.